Outras vozes da política: memória e imaginação - José Luiz Bica de Mélo (Ciências Sociais Unisinos)
The text aims to present the relation between reason and sensibility through a brief path of literary and poetic reflection, trying to think about the nexus between politics and imagination. Taking the relational analysis of the poem “El sur también existe” by Mario Benedetti as a reference and inviting the reader to read poems by Octavio Paz, Martha Nélida Ruiz, Gregory Bateson and Etienne Samain, it also suggests that the social scientist should take into consideration the relations between fiction and socio-historical reality and memory as connections that aim at the web of life which we conventionally call society.